2020
DOI: 10.1007/s00415-020-09928-8
|View full text |Cite
|
Sign up to set email alerts
|

Wearable sensors can reliably quantify gait alterations associated with disability in people with progressive multiple sclerosis in a clinical setting

Abstract: Gait disability in people with progressive multiple sclerosis (MS) is difficult to quantify using existing clinical tools. This study aims to identify reliable and objective gait-based biomarkers to monitor progressive multiple sclerosis (MS) in clinical settings. During routine clinical visits, 57 people with secondary progressive MS and 24 healthy controls walked for 6 minutes wearing three inertial motion sensors. Fifteen gait measures were computed from the sensor data and tested for between-session reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 54 publications
7
59
0
Order By: Relevance
“…Moreover, another study highlighted excellent reliability during a 6MWT (without the specific instruction to walk as long-distance as possible) with several walking parameter values acquired with small inertial sensors. In this study, the higher the EDSS score, the more the reliability was increased [27], which may explain the good to excellent reliability values in our study in persons with severe MS.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Moreover, another study highlighted excellent reliability during a 6MWT (without the specific instruction to walk as long-distance as possible) with several walking parameter values acquired with small inertial sensors. In this study, the higher the EDSS score, the more the reliability was increased [27], which may explain the good to excellent reliability values in our study in persons with severe MS.…”
Section: Discussionsupporting
confidence: 49%
“…Although several studies have highlighted good reliability of the 6MWT score (i.e., the distance traveled in meters measured only one time at the end of the 6MWT) [16], little is known about the reliability of the ST variables across the 6MWT in PwMS with several measures during the 6MWT [27]. Moreover, to our knowledge, no study has analyzed the reliability of perceived exertion during the 6MWT (e.g., using the Borg scale).…”
Section: Introductionmentioning
confidence: 99%
“…Walking stability during natural walking have been used to quantify the balance ability and disease severity, which can be accessed using wearable sensors without the limitations of a gait laboratory environment [11][12][13]. The sensor-based measurements of walking stability include acceleration root mean square (RMS) harmonic ratio (HR), gait variability, gait symmetry and gait regularity [14].…”
Section: Introductionmentioning
confidence: 99%
“…In a direct comparison of the Mobility Lab with the GAITRite system, Schmitz-Hübsch et al have demonstrated that the portable sensors meet the criteria for validity, reliability and objectivity (Schmitz-Hübsch et al, 2016). A recent work has confirmed that the opal sensors are reliable in test-retest analysis and suitable for clinical use (Angelini et al, 2020). We use six portable sensors for the analysis of balance carrying out the Romberg test and for the detailed analysis of different spatial and temporal gait parameters during the 2-MWT.…”
Section: Infrastructurementioning
confidence: 99%